Ice Flavor-Related Discussions on Twitter: Content Analysis - Artur Galimov; Julia Vassey; Ellen Galstyan; Jennifer B Unger; Matthew G Kirkpatrick; Jon-Patrick Allem (JMIR Publications, 2022)
BackgroundThe US Food and Drug Administration (FDA) recently restricted characterizing flavors in tobacco products. As a result, ice hybrid-flavored e-cigarettes, which combine a cooling flavor with fruit or other flavors (eg, banana ice), emerged on the market. Like menthol, ice-flavored e-cigarettes produce a cooling sensory experience. It is unclear if ice hybrid-flavored e-cigarettes should be considered characterizing flavors or menthol, limiting regulatory action. Monitoring the public's conversations about ice-flavored e-cigarettes on Twitter may help inform the tobacco control community about these products and contribute to the US FDA policy targets in the future. ObjectiveThis study documented the themes pertaining to vaping and ice flavor-related conversations on Twitter. Our goal was to identify key conversation trends and ascertain users' recent experiences with ice-flavored e-cigarette products. MethodsPosts containing vaping-related (eg, "vape," "ecig," "e-juice," or "e-cigarette") and ice-related (ie, "Ice," "Cool," "Frost," and "Arctic") terms were collected from Twitter's streaming application programming interface from January 1 to July 21, 2021. After removing retweets, a random sample of posts (N=2001) was selected, with 590 posts included in the content analysis. Themes were developed through an inductive approach. Theme co-occurrence was also examined. ResultsMany of the 590 posts were marked as (or consisted of) marketing material (n=306, 51.9%), contained positive personal testimonials (n=180, 30.5%), and mentioned disposable pods (n=117, 19.8%). Other themes had relatively low prevalence in the sample: neutral personal testimonials (n=45, 7.6%), cannabidiol products (n=41, 7%), negative personal testimonials (n=41, 7%), "official" flavor description (n=37, 6.3%), ice-flavored JUUL (n=19, 3.2%), information seeking (n=14, 2.4%), and comparison to combustible tobacco (n=10, 1.7%). The most common co-occurring themes in a single tweet were related to marketing and disposable pods (n=73, 12.4%). ConclusionsOur findings offer insight into the public's experience with and understanding of ice-flavored e-cigarette products. Ice-flavored e-cigarette products are actively marketed on Twitter, and the messages about them are positive. Public health education campaigns on the harms of flavored e-cigarettes may help to reduce positive social norms about ice-flavored products. Future studies should evaluate the relationship between exposure to personal testimonials of ice-flavored vaping products and curiosity, harm perceptions, and experimentation with these products among priority populations.